Pengaruh Kualitas Pelayanan Dosen Dan Fasilitas Perkuliahan Terhadap Kepuasan Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Roy Hanafi; Muhammad Mansur; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract               This study aims to determine the effect of lecturer service quality and lecture facilities on Faculty of Economics and Business, Islamic University of Malang student satisfaction. The data used in this study uses primary data by distributing questionnaires to respondents. The study population was students of the Faculty of Economics and Business UNISMA, while the sample used was the Management Study Program, Accounting and Sharia Banking in the 2016-2018 class year at the Faculty of Economics and Business, Islamic University of Malang. The research sample was taken from the population using a sampling technique in the form of a purposive sampling method. The results obtained by using multiple linear regression test Y = -5,933 + 0,287 x_1 + 0,313x_2 + e, and this research test uses the f test and t test. The results of this study indicate that the quality of lecturer services partially influences student satisfaction and lecture facilities affect student satisfaction. While simultaneously the quality of lecturer services and lecture facilities affect student satisfaction. Key words: Lecturer Service Quality, Lecture Facilities and Student Satisfaction